HIV status disclosure patterns and male partner reactions among pregnant women with HIV on lifelong ART in Western Kenya. Issue 7 (2nd July 2020) - Abuogi, Lisa; Hampanda, Karen; Odwar, Tobias; Helova, Anna; Odeny, Thomas; Onono, Maricianah; Bukusi, Elizabeth; Turan, Janet
ABSTRACT: Disclosure of HIV status to sexual partners in the context of prevention of mother-to-child transmission (PMTCT) may contribute to improved PMTCT outcomes. We administered a questionnaire to 200 women with HIV enrolled in a PMTCT study during pregnancy at 12 months after birth in Western Kenya between May-September 2017. Descriptive analysis of disclosure patterns and multivariate analysis of factors associated with male partner reactions is presented. Among 180 (90%) women who reported having a male partner, 95.5% reported disclosing their HIV status to that partner. The majority of women (82.8%) reported disclosure occurred within one year of their diagnosis, with 62.7% occurring within one week. The most common forms of disclosure were: self-disclosure (55.4%), during couple's HIV testing and counseling (CHTC) (31.5%), or at an antenatal care visit (7.7%). Most women (87.5%) reported that male partner reactions to their HIV status disclosure were positive. Those with negative reactions reported their partners were confused, annoyed, or threatened to leave, however there were no reports of intimate partner violence (IPV) or break ups. Disclosure via CHTC was associated with a positive male partner reaction compared to self-disclosure (adjusted OR (aOR) 20.2, 95% Confidence Interval (CI) 1.8–221.4). Those in concordant HIV status partnerships were more likely to have a positive reaction (aOR. 6.7, 95% CI 1.7–26.6). Women experiencing frequent verbal IPV were less likely to report a positive response (aOR 0.21, 95%CI 0.1–0.8). Most postpartum women with HIV in this cohort had disclosed to their male partners early after diagnosis and experienced a positive reaction. However, a minority had still not disclosed by 12 months after the birth and some experienced negative reactions to disclosure. The form of status disclosure and impact of intimate partner violence should be given greater attention within the context of PMTCT.